Tornar-se cuidadora: relatos de familiares sobre a vivência do cuidado paliativo domiciliar - Borges, Veronica Gomes Assunção (2021)
By taking on the role of caregiver in home care, the family member undertakes multitasks related to the direct management of the person who is being cared for, for which they were not prepared. The long-term home care of a totally dependent family member demands learning, adjustments, and new perspectives on oneself and the other. In order to help with the process of hospital discharge, the Home Care Service remains on the rear of patient and family care, being, at many times, their only support system. In this context, this study aimed at understanding the routine of family members who experience long-term palliative home care. Five family caregivers, assisted by the “Melhor em Casa” program in the city of Uberlandia, in Minas Gerais, were interviewed. This interview was guided by the thematic life story modality, then textualized and transcreated in a second meeting with the participants what made possible to understand the experience on the theme in the light of each one's life trajectory. The analysis of the material allowed the formation of the thematic categories: (1) Getting sick, the hospitalization and the hospital-home transition; (2) Being at home: adapting to the environment, the caring routine, and the demands of the caregiver figure; (3) Becoming and being a caregiver and the changes of home care over time; (4) Taking care during the pandemic; (5) Support System and support; (6) From caregiver to caregiver. Taking care of someone who has been present throughout the life history of the caregivers, responsible for siblings and for maintaining the house since their childhood. The caregivers experienced caring between one and 17 years at home, they were mothers, daughters, or sisters of relatives with severe neurological sequelae, using devices such as tracheostomy or feeding tube, needing for management with suction, diets, and bed positioning. The relative’s health condition required caregivers to perceive the wants and needs of those who were being cared for, in order to promote comfort and quality of life. The categories addressed issues related to the process of in-hospital and home living, the hospital was the place where the caregivers learned about the necessary daily care and had information regarding the prognosis of the family member. During the hospital discharge process, the caregivers waited for a preparatory course and only a brief orientation, with that there was insecurity and fear in the initial process at home. The caregivers demonstrate a preference for care at home, which has undergone environmental adjustments to receive the family member and was identified as a place of comfort, referred to as home, which allows for a routine to be established, whose intensity of demand is lessened over the years. Caring happens in a solitary way, with the “Melhor em Casa” program being the main support system. For care to happen, several reformulations were necessary, such as seeing a new person and learning to love them the way they are. Living with someone who is totally dependent on the care of the family member makes this process of care difficult, with physical and emotional consequences.